The Impact of Federalization on Health Sector in Nepal: New Opportunities and Challenges: New opportunities and challenges - Vaidya, Anju; Simkhada, Padam; Simkhada, Bibha (Journal of Nepal Health Research Council, 2020)
The promulgation of constitution of Nepal in 2015 has shifted the unitary government of Nepal towards federalism with significant devolution of power to seven newly created provinces, each with their own unicameral legislature. The major challenges during the transition phase in health sector are spillover effects, unclear roles and responsibilities of local authorities, human resource management and strengthening capacity at local level as per local need. Despite these challenges, federalism brings fertile ground for the local government to work more closely with their people; with more effective financing and planning based on evidences and their need. Keywords: Federalism; health sector; Nepal; challenges; opportunities.